2020
DOI: 10.1002/nag.3088
|View full text |Cite
|
Sign up to set email alerts
|

Digital spatial cracking behaviors of fine‐grained sandstone with precracks under uniaxial compression

Abstract: SummaryX‐ray computed tomography (CT) imaging and digital image correlation techniques are applied to study spatial cracking behaviors of sandstone under uniaxial compression, in which the angle between precracks is 45°, 90°, and 135° and the crack depth is 7.5 mm and 10 mm, respectively. Layered anisotropy damages and spatial cracking evolution are quantitatively analyzed by the defined digital layered anisotropy index and digital damage ratio, respectively. Three cases with different array of precracks evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Secondary cracks are the main cause of specimen damage. For a single-flaw specimen, it has been shown 34,[44][45][46] that most of the first and secondary crack initiation locations are located at the tip of the flaw. However, the influence degree of the first and secondary crack on the orthogonal cross flaws specimens is different under different α; therefore, the initiation locations of the first cracks and secondary cracks are different.…”
Section: Crack Initiation Positionmentioning
confidence: 99%
“…Secondary cracks are the main cause of specimen damage. For a single-flaw specimen, it has been shown 34,[44][45][46] that most of the first and secondary crack initiation locations are located at the tip of the flaw. However, the influence degree of the first and secondary crack on the orthogonal cross flaws specimens is different under different α; therefore, the initiation locations of the first cracks and secondary cracks are different.…”
Section: Crack Initiation Positionmentioning
confidence: 99%
“…In a study by , three-dimensional observation of fine structural changes in a bi-soil body under triaxial compression using CT scanning tests demonstrated that changes in local mechanical properties significantly influence the development and propagation of overall cracks. Zhou et al (2020) used X-ray computed tomography imaging and digital image correlation techniques to examine the seismic cracking behavior of sandstone under uniaxial compression. They quantitatively analyzed the layered anisotropic damage and spatial crack evolution using the defined numerical anisotropic damage index and numerical damage rate, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture mechanisms, including displacement discontinuities, shear band characteristics and crack interfaces, are also analyzed by the DIC technology [27][28][29][30]. Zhou et al studied crack types, real-time cracking behaviors, and mechanical properties by X-ray CT and DIC techniques in which five cracking stages were divided [31]. Bésuelle et al used high resolution, fast X-ray micro tomography (synchrotron radiation) to evaluate the onset and evolution of strain localization in Callovo-Oxfordian argillite under deviatoric loading and focused on the ductile behavior at higher confining stress [32].…”
Section: Introductionmentioning
confidence: 99%